Effectiveness of NSP enzyme and organic chromium supplementation in low-protein feed on carbohydrate utilization in Pomfret Colossoma macropomum - Faiqotul Himmah, Maihardiyanti; Achmad Fauzi, Ichsan; Ekasari, Julie; Raditya Gumelar, Muhammad; Muhammad Agus Suprayudi (Jurnal Akuakultur Indonesia, 2025)
This study aims to evaluate the effectiveness of NSP enzyme and organic chromium supplementation in low-protein Colosoma macropomum diet to increase carbohydrate utilization. The diets contains isoprotein (20%) and isoenergy. Factorial design with two factors, namely NSP enzyme (0 and 1 g/kg) and organic chromium (0, 1, and 2 mg/kg). Fish are reared in an aquarium measuring 80 x 50 x 35 cm3 and containing 75 L of water and stock at the density of 15 fish and reared for 60 days. The test parameters used are postprandial blood glucose levels, antioxidant activity, glycogen in muscle and liver, and growth performance. The results showed that the highest postprandial blood glucose levels were when the NSP enzyme was administered. Furthermore, the lowest malondialdehyde (MDA) values and the highest superoxide dismutase (SOD) and glutathione peroxide (GPx) values were obtained in fish fed feed containing 1 g/kg of NSP enzyme and 1 mg/kg organic chromium. Fish fed feed containing 1 g/kg NSP enzyme and 1 mg/kg organic chromium showed significant values in liver and muscle glycogen as well as growth performance compared to other treatments. From this research, it can be concluded that supplementation of NSP enzyme and organic chromium at doses of 1 g and 1 mg per kg of feed produces the best growth performance and anti-oxidant capacity in pomfret fish. Keywords: antioxidant, glycogen, growth performance, postprandial blood glucose ABSTRAK Penelitian ini bertujuan untuk mengevaluasi efektivitas suplementasi enzim NSP dan kromium organik pada pakan ikan bawal Colosoma macropomum rendah protein untuk meningkatkan pemanfaatan karbohidrat. Pakan yang digunakan mengandung iso protein (20%) dan isoenergi. Rancangan faktorial dengan dua faktor yakni enzim NSP (0 dan 1 g/kg) dan kromium organik (0, 1, dan 2 mg/kg). Ikan bawal dipelihara dalam akuarium dengan ukuran 80 x 50 x 35 cm3 dan berisi air 75 L diisi 15 ekor ikan dan dipelihara selama 60 hari. Adapun parameter uji yang digunakan adalah pengukuran kadar glukosa darah postprandial, aktivitas antioksidan, glikogen, dan kinerja pertumbuhan. Hasil penelitian menunjukkan kadar glukosa darah postprandial tertinggi pada pemberian enzim NSP. Selanjutnya nilai malondialdehyde (MDA) terendah dan superoxide dismutase (SOD) dan glutathione peroxide (GPx) tertinggi didapat pada ikan yang diberi pakan mengandung pada 1 g/kg enzim NSP dan 1 mg/kg kromium organik. Ikan yang diberi pakan yang mengandung 1 g/kg enzim NSP dan 1 mg/kg kromium organik menunjukkan nilai signifikan pada glikogen hati dan otot serta kinerja pertumbuhan dibanding perlakuan lainnya. Dari penelitian ini dapat disimpulakan bahwa suplementasi enzyme NSP dan Kromium organik pada dosis 1 g dan 1 mg per kg pakan menghasilkan kinerja pertumbuhan dan kapasitas antioksidan terbaik pada ikan bawal. Kata kunci: antioksidan, glikogen, glukosa darah postprandial dan kinerja pertumbuhan